People of Lower Social Status Are More Sensitive to Hedonic Product Information—Electrophysiological Evidence From an ERP Study - Chen, Di; Qu, Weiguo; Xiang, Yanhui; Zhao, Jiaxu; Shen, Guyu (Frontiers in Human Neuroscience, 2019)
Consumer psychology research have found that individuals of different social status have different purchase intentions for different products. Individuals of high social status will simultaneously measure the status symbolic meaning and utilitarian value of the product, but they won’t show strong preferences for certain attributes; however, individuals of low social status show a strong purchasing tendency for hedonic products which contain status symbolic meanings and which satisfy their spiritual needs. This phenomenon may be due to their self-threat, which is caused by hedonic products. Based on the above, this study is the first to explore the cognitive process difference of hedonic and utilitarian label products in high- and low-social-status groups by recording event related potentials (ERPs). The result showed that under the P2, P3 and LPP components, low-social-status group elicited more negative deﬂections in hedonic label stimuli than in utilitarian label stimuli, while high-social-status group did not have significant difference in these components. These suggested that humans with low social status are more sensitive to hedonic products information, because high-status information contained in the hedonic label brings a sense of threat to them and generates their certain negative emotions, which make them preferentially process such information in the information processing.